(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate sexual dysfunction in female patients with depression treated as outpatients at the Institute of Mental Health, Bach Mai Hospital. Method: Cross-sectional study of 80 female patients with depression treated as outpatients at the Institute of Mental Health, Bach Mai Hospital from 2/2023 to 1/2024. Results: 80 subjects aged 18-50 years old, with an average age of 28.21 ± 1.01. 53.8% of patients were diagnosed with severe depression. 47% of patients with depression had reduced sexual frequency since the onset of the disease, 60% of patients had less than 1 sexual intercourse in the past 4 weeks. Comparing the mean FSFI score and the component scores in the 6 factors of the 2 groups, found that the factors of desire and discharge had a statistically significant difference, there was no difference between the factors of orgasm and sexual satisfaction. Conclusions: Sexual dysfunction is a common problem in depressed patients, 90% of female depressed patients have sexual dysfunction according to the FSFI scale. The difference is statistically significant in the index of desire and discharge between the two groups of depression and non-depression according to the BECK scale.